Aspek Religi Pada Novel Bumi Cinta Karya Habiburrahman El Shirazy: Tinjauan Semiotik Serta Implementasinya Dalam Pembelajaran Sastra Di SMA - Listyani, Adelika Pratnya; , Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
This thesis aims at giving (1) description in Social culture background of Habiburrahman El- Shirazy, (2) explanation in constructive structure of Bumi Cinta novel, (3) explanation in religious value of Bumi Cinta novel in poem collection is teaching by semiotic literatute (4) implementation in religious value of Bumi Cinta novel in literature learning in senior high school. The method of observation use qualitative descriptive. The data of observation are words and sentences. The source of observation is Bumi Cinta novel by Habiburrahman. The technique of collecting data are pustaka technique, reading and writing. The technique of analyzing data use semiotic model of reading consist of heuristic and hermenuitic. There are four results in this observation (1) Habiburrahman El Shirazy was born on Semarang, thursday September, 30th 1976. The creation of Habiburrahman El Zhirazy is popular in the movie. (2) the structure of novel are theme, cheater, plot, dan place. (3) Religious value Bumi Cinta novel are consist of relogious emotional, credibility system and relogious ceremony system. (4) this observation can be implementaion in literature learning in eleventh students of Senior high school in fisrt semester. There are good criteria material in Bumi Cinta novel, they are: point of view language, maturity psychic ( psychological) and culture background. Keywords: Religious value, novel, literature learning in SMA, semiotic.